Does The Crude Palm Oil Market Walk Randomly? - Dolly Parlagutan Pulungan; Sugeng Wahyudi; Suharnomo Suharnomo (University of Merdeka Malang, 2018)
Study about the efficiency of the capital market has been extensively conducted, but it is still lack of research on the efficiency of other financial markets such as commodity markets. This study specifically examines market efficiency in a weak form in a commodity market, especially in the crude palm oil (CPO) market. The purpose of this research is to analyze the weak form efficiency of the CPO market. Data used in this research is monthly CPO closing price data in 2010-2017 from Bursa Malaysia Derivative Exchange (BMD). This data was obtained from the Malaysian Palm Oil Council (MPOC). The analysis tool used is Runs Test, following by Unit Root Test and Correlogram as robustness checking. The result of this study shows that the CPO market is being efficient in a weak form. This shows that CPO price walks randomly so that the technical analysis cannot be applied to predict the CPO price. The result of this study suggests to both of CPO traders, and CPO speculators in their transaction on BMD do not rely on technical analysis.JEL Classifications: G14; Q02DOI: https://doi.org/10.26905/jkdp.v22i2.2023